Intermittent and short duration ultrasound in a simulated porous medium - Augustine Agi; Radzuan Junin; Mohd Faddli Syamsul; Aik Shye Chong; Afeez Gbadamosi (Petroleum, 2019)
Ultrasound is an unconventional method used to recovery oil, despite the report on the use of this technique, the focus has always been on the continuous application of ultrasound. But the continuous ultrasound has its own limitation of high cost of production and maintenance of equipment because of high energy generated. In this study, the use of short duration, intermittent ultrasound was investigated, and the result compared with the continuous ultrasound. The effect of viscosity and intensity on both intermittent and continuous ultrasound was also investigated. A 2D micro-model placed inside an ultrasonic bath under an ultrasound radiation was used, a stereo microscope with the camera mounted at the top of the micro-model recorded the displacement process. The snapshot of each time interval was used to give the estimate in percentage (%) of the residual oil left in the micro-model. The results show that, short duration and intermittent ultrasound can recover more oil compared with the application using continuous ultrasound and longer duration. Therefore, the use of intermittent ultrasound as a green and cost-effective technique is herein proposed. Keywords: Ultrasonic, Intermittent ultrasound, Continuous ultrasound, Micro-model, Porous media, Enhanced oil recovery